About Alexander Fedorovitch Mukhin, the Great Patriotic War Veteran, Grounder of the Account and Statistics School in MGIMO - N. E. Grigoruk; S. I. Putchkova; N. N. Liventzev (Vestnik MGIMO-Universiteta)
.